ПРАКТИЧЕСКИЕ ВОПРОСЫ СОХРАНЕНИЯ БИОРАЗНООБРАЗИЯ РЫБ В ВОДОЕМАХ ОСОБО ОХРАНЯЕМЫХ ПРИРОДНЫХ ТЕРРИТОРИЙ (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In work ways of the decision of the problem questions connected with the organization offishery, by carrying out рыгбохозяйственной land improvements, working out ofplans for development of a fish economy and carrying out of researches under programs of Annals of the nature in reservoirs of especially protected natural territories are discussed.